Tribes, forest, and social formation in Indian history - Chaudhuri,B.B.(Editor) Arun Bandoopadhyay.(Editor) (Manohar, 2004)
Mostly revised versions of papers presented at the panel "Tribes, Forests, and Social Formation in Indian History" at the Bhopal Session (2001) of Indian History Congress.